Engineering of konjac glucomannan into respirable microparticles for delivery of antitubercular drugs - Guerreiro, Filipa (2022)
Few medically-approved excipients are available for formulation strategies to endow microcarriers with improved performance in lung drug targeting. Konjac glucomannan (KGM) is a novel, biocompatible material, comprising mannose units potentially inducing macrophage uptake for the treatment of macrophage-mediated diseases. This work investigated spray-dried KGM microparticles as inhalable carriers of model antitubercular drugs, isoniazid (INH) and rifabutin (RFB). The polymer was characterised and different polymer/drug ratios tested in the production of microparticles for which respirability was assessed in vitro. The swelling of KGM microparticles and release of drugs in simulated lung fluid were characterised and the biodegradability in presence of beta-mannosidase, a lung hydrolase, determined. KGM microparticles were drug loaded with 66-91% association efficiency and had aerodynamic diameter around 3 mu m, which enables deep lung penetration. The microparticles swelled upon liquid contact by 40-50% but underwent size reduction (>62% in 90 min) in presence of beta-mannosidase, indicating biodegradability. Finally, drug release was tested showing slower release of RFB compared with INH but complete release of both within 24 h. This work identifies KGM as a biodegradable polymer of natural origin that can be engineered to encapsulate and release drugs in respirable microparticles with physical and chemical macrophage-targeting properties.